Epidemiology of Leprosy in Spain: The Role of the International Migration. - José M Ramos; David Romero; Isabel Belinchón (Public Library of Science (PLoS), 2016)
BACKGROUND:Although incidence of leprosy in Spain has declined steadily over the years, the fivefold increase in immigration since the turn of the century--much of it from countries where leprosy is still prevalent--has been linked to an uptick in registered cases. OBJECTIVE:To describe the epidemiologic trends of incident leprosy cases detected in Spain among Spanish- and foreign-born population groups. METHODS:Observational, retrospective study of suspected leprosy cases in Spain, as reported through the System of Compulsory Notification of Diseases from 2003 to 2013, with results disaggregated by country of birth. We collected statistical data on leprosy burden for other countries from WHO to estimate the expected number of imported cases. RESULTS:Of the 168 leprosy cases registered during the study period, 40 (24.6%) were in Spanish patients, while 128 (76.2%) were detected in legally resident immigrants. We identified a significantly higher number of imported leprosy cases during the 2008-2010 and 2011-2013 trienniums compared to the reference biennium 2003-2004 (OR 5.38, 95% CI 1.83-14.88 and OR 4.80, 95% CI 1.41-16.33, respectively). Most imported cases were diagnosed in Latin American immigrants (71.9%), especially Brazilians, but also Paraguayans, Bolivians and other nationalities from South and Central America. However, registered incidence was lower than expected for each year. For example, in 2003, the expected new cases in immigrants was 47.12, compared to only four cases that were actually detected (a 91% difference). Likewise, we expected to find 49.6 incident cases among immigrants in 2009, but only 15 new cases were reported (60% fewer than expected). CONCLUSION:Imported cases of leprosy are responsible for most leprosy incidence in Spain, and we cannot rule out some under-diagnosis. Clinicians should be made more aware of the potential for leprosy incidence among patients from countries where the disease is endemic.